Kenya gender strategy: Building equitable climate-resilient African bean & insect sectors - Wambua, Scholastica; Karanja, David; Lutomia, Cosmas; Nyamolo, Victor; Ouya, Frederick; Ketema, Dessalegn; Nchanji, Eileen (2025)
The Building Equitable Climate-Resilient African Bean and Insect Sectors (BRAINS) project is a multi-country initiative operating across 15 Sub-Saharan African countries, including Kenya. BRAINS aims to foster low-carbon, climate-resilient agrifood systems in the bean, fruit tree, and insect sectors by equitably enhancing climate resilience among women and youth, scaling the adoption of climate-smart agriculture technologies, and building a pipeline of gender-responsive, climate-resilient enterprises aligned with emerging climate finance goals.